Nuevas estrategias farmacológicas en la enfermedad de Alzheimer: la hiperactividad y la neuroinflamación como nuevos blancos potenciales - Lobos Z., Pedro; More C., Jamileth; Bruna J., Bárbara; Penna S., Antonello (Revista Hospital Clínico Universidad de Chile, 2023)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by the progressive deterioration of cognitive functions such as memory, language, executive function, and visuospatial function, starting from the late ages of life (> 65 years). The etiology of AD is multifactorial involving the interaction of genetic, environmental, and systemic factors. Histopathologically characterized by the progressive accumulation of peptide Aβ and TAU protein. Markers of damage that begin to accumulate decades before symptoms can be detected. However, during the early stages of the disease, systemic inflammation and cortical/hippocampal hyperactivity have been revealed present in patients. In the following review, we present a perspective on how neuroinflammatory processes and pathological cortical hyperexcitability contribute to the onset and development of the early stages of AD. We present a current summary of the basic and clinical evidence that allows us to understand the complexity and heterogeneity of this pathology. Finally, we briefly collect and analyze the main therapeutic strategies that have been studied to reduce the phenotype of neuronal hyperactivity directly or indirectly.